Risk assessment : tools, techniques, and their applications - Ostrom, Lee T.; Wilhelmsen, Cheryl A., 1953- (Wiley, 2019)
"Since the first edition of our book was published there have been several changes in the types of risk individuals, businesses, and governments are being exposed to. Cyber-attacks are more frequent and costly and lone-wolf style terrorist attacks are more common; events not addressed in the first edition. The book continues to provide a resource that leads the reader through a risk assessment and shows them the proper tools to be used at the various steps in the process. This book also provides students studying safety and risk assessment a resource that assists them in understanding the various risk assessment tools. The book provides readers with a toolbox of techniques that can be used to aid them in analyzing conceptual designs, completed designs, procedures and operational risk. On top of the ten new chapters the new edition also includes expanded case studies and real life examples; coverage on risk assessment software like SAPPHIRE and RAVEN; and end-of-chapter questions for students with a solutions manual for academic adopters. The approach to the book remains the same and is analogous to a toolkit. The user locates the tool that best fits the risk assessment task they are performing. The chapters of the book progress from the concept of risk, through the simple risk assessment techniques, and into the more complex techniques. In addition to discussing the techniques, this book presents them in a form that the readers can readily adapt to their particular situation. Each chapter, where applicable, presents the technique discussed in that chapter and demonstrates how it is used"--
Keywords: rizikový management; statistické metody; riziková analýza; risk management; statistical methods; risk analysis; učebnice; textbooks